Effect of Put on Different Levels of Anise and Clove Oil Added to Broiler Feed on Some Biochemical Traits of Blood, Carcass and Dressing Percentage (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: This experiment was conducted to study the effect of adding anise and clove oil on the physiological performance of broiler, represented by biochemical traits and carcass components, for a period of 35 days.Materials and Methods: In this experiment 300 Ross 308 broiler chicks One-day old were used. The chicks were randomly distributed into six equal treatments with two replicates for each treatment (25 birds per replicate). The birds were divided into treatments as follows: The first treatment (T1) basic diet, second and third treatment (T2 and T3) basic diet with anise oil added at 0.5 and 0.1 ml/kg feed respectively, fourth and fifth treatment (T4 and T5) basic diet with clove oil added at 0.5 and 0.1 ml/kg feed respectively, and sixth treatment (T6) basic diet with 0.5 ml/kg of each anise and clove oil. Some biochemical traits of blood, carcass and dressing percentage were measured. Results: The results of the experiment showed that adding anise oil, clove oil and their mixture had a significantly excelled (P